Cultivating Resilience in East and Southern Africa Through Climate-Smart Seeds - Thierfelder, Christian L.; Nkosi, Phindiwe (CGIAR System Organization, 2023)
This is a blog about how Southern and Eastern Africa can capture genetic gains to improve resilience of farming systems through use of improved seed/stress-tolerant or climate-resilient seeds.